2015
DOI: 10.1007/s10103-015-1801-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects of λ = 808 nm GaAlAs diode laser irradiation on different titanium surfaces

Abstract: Diode lasers are widely used in dental laser treatment, but little is known about their thermal effects on different titanium implant surfaces. This is a key issue because already a 10 °C increase over the normal body temperature can induce bone injury and compromise osseo-integration. The present study aimed at evaluating the temperature changes and surface alterations experienced by different titanium surfaces upon irradiation with a λ = 808 nm diode laser with different settings and modalities. Titanium dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…During the treatment, the temperature was recorded by a thermal probe included in the laser system console and monitored by a thermal camera (Ti9, Fluke Corp., Everett, WA, USA) showing a thermal map of the irradiated area (data not shown). The temperature remained unchanged during PBM treatments, as previously reported [ 84 , 85 ]. For the duration of PBM treatments, the cover cell culture plate was removed, and all the procedures were carried out under “clean bench” conditions to prevent contamination.…”
Section: Methodssupporting
confidence: 84%
“…During the treatment, the temperature was recorded by a thermal probe included in the laser system console and monitored by a thermal camera (Ti9, Fluke Corp., Everett, WA, USA) showing a thermal map of the irradiated area (data not shown). The temperature remained unchanged during PBM treatments, as previously reported [ 84 , 85 ]. For the duration of PBM treatments, the cover cell culture plate was removed, and all the procedures were carried out under “clean bench” conditions to prevent contamination.…”
Section: Methodssupporting
confidence: 84%
“…The authors demonstrated that while the used parameters did not change the treated surfaces, 3 W was 100% effective for surface decontamination [ 203 ]. The thermal effects of diode lasers (810 nm and 980 nm) when used at low energy (1 W) in pulsed mode with air/water cooling maintained the temperature below the critical threshold of 47 °C [ 204 , 205 , 206 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, no surface alterations were found for the 445 nm wavelength when radiating for 4 min at 2.0 W with a distance of 1 mm to the discs. Surface alterations on titanium discs and dental implants have been reported in other studies using different wavelengths, distances to the object, and power settings [12,13,14,21]. Romanos et al [12] showed that using Nd:YAG (1064 nm wavelength) at 2.0 W and 4.0 W in contact resulted in, as they describe it, melting and damage to the surface of the discs.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies done in vitro on temperature increases in and around dental implants have shown great discrepancies between different wavelengths of lasers [10,11]. Also, studies on alterations of the dental implant surface show conflicting results as to which wavelength of lasers should be used with limited risk for damaging the dental implant [12,13,14]. To our knowledge, no studies have yet looked at the potential deleterious effects of the 445 nm wavelength when directly irradiating a dental implant.…”
Section: Introductionmentioning
confidence: 99%